2012
DOI: 10.1308/003588412x13171221501861
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for music in reducing anxiety in plastic surgery minor operations?

Abstract: In the era of the patient centred approach to clinical care, it is crucial to minimise patient anxiety. Music appears to reduce intra-operative anxiety in awake patients in both the elective and trauma plastic surgical setting. Easy listening music and chart classics appear to be suitable genres according to patients. We believe there is a role for a large, multicentre, randomised control study to examine the benefits of music in all local anaesthetic procedures across different specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…30,31 A randomized study of patients undergoing colposcopy found lower anxiety and pain score in patients who listened to music than in a control group. Two recent studies have shown that music reduces patient anxiety during minor plastic surgery procedures requiring local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 A randomized study of patients undergoing colposcopy found lower anxiety and pain score in patients who listened to music than in a control group. Two recent studies have shown that music reduces patient anxiety during minor plastic surgery procedures requiring local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have shown that music reduces patient anxiety during minor plastic surgery procedures requiring local anesthesia. 30,31 A randomized study of patients undergoing colposcopy found lower anxiety and pain score in patients who listened to music than in a control group. 32 In a meta-analysis of six studies examining the effect of music during endoscopic procedures, patients who listened to music exhibited lower anxiety levels and required lower doses of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin pigment that disappears when bleached is typically found within the black or brown lesions found throughout the bladder. 2 …”
Section: Discussionmentioning
confidence: 99%
“…3 Smartphone ownership and use among the medical profession is widespread. 4 5 Digital music is therefore readily available in the workplace.…”
mentioning
confidence: 99%